2012
DOI: 10.1016/j.enpol.2012.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Oil and gas trends and implications in Malaysia

Abstract: a b s t r a c tThe trends of reserves, production and consumption of oil in Malaysia to meet the ever-increasing demands do not seem to show that oil and gas will be depleted soon, contrary to many reports. Malaysia's net exporter status of oil continues to expand over time for as long as the value of exports is greater than the value of imports. Only in physical quantities of oil that Malaysia's imports exceed exports, but this does not mean that Malaysia will be a net importer by then. Given higher prices of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 2 publications
2
17
0
Order By: Relevance
“…The basic structure of Malaysian economic and productive development is highly dependent on the consumption of fossil fuel, and the main sources of energy supply are petroleum and natural gas, both accounting for more than 88% of the total energy supply [12]. At the current consumption rate, the projected reservation of petroleum and natural gas in Malaysia would last for the next 16 and 36 years.…”
Section: Introductionmentioning
confidence: 99%
“…The basic structure of Malaysian economic and productive development is highly dependent on the consumption of fossil fuel, and the main sources of energy supply are petroleum and natural gas, both accounting for more than 88% of the total energy supply [12]. At the current consumption rate, the projected reservation of petroleum and natural gas in Malaysia would last for the next 16 and 36 years.…”
Section: Introductionmentioning
confidence: 99%
“…During the same period, oil production and consumption has increased by 50% and 200% respectively whilst gas production and consumption has increased by 400% [1]. As of 2012, Malaysia has proven oil reserves of 4 billion barrels (bbl), with a reserve-to-production ratio of 17.08 years, whilst proven gas reserves stand at 83 trillion cubic feet (tcf) with a reserve-to-production ratio of 34.14 years [1], [2].…”
Section: A Backgroundmentioning
confidence: 99%
“…For gas production and consumption, it is seen that the general trend is increasing at the rate of 3 to 5% annually. With consumption trend based on 1998-2010 oil and gas consumption, it is forecasted that the oil reserves and gas reserves are expected to last until 2035 and 2050 respectively [1], [2].…”
Section: Current Oil and Gas Trends And Future Predictionsmentioning
confidence: 99%
“…Acemoglu, Johnson, and Robinson (2001) emphasize that Botswana's good governance institutions were motivation for its remarkable long-run economic development. Another example is studied by Rahim and Liwan (2012), where it is empirically shown that Malaysia seems to have succeeded in establishing sustainable economic development by managing its natural resource through good governance indicators.…”
Section: Developments In Natural Resources and Governance In Postmentioning
confidence: 99%